2003
DOI: 10.1093/brain/awg112
|View full text |Cite
|
Sign up to set email alerts
|

Source versus content memory in patients with a unilateral frontal cortex or a temporal lobe excision

Abstract: It has been suggested previously that patients with a frontal lobe lesion might have a specific impairment in the retrieval of the source of information despite adequate memory for facts. Patients with an anterior temporal excision are known to have impairments in memory for facts and the question arises as to whether they are also impaired in source memory. The present study compared memory for facts and their source in patients with a unilateral frontal cortical or an anterior temporal excision in a situatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 38 publications
2
18
0
1
Order By: Relevance
“…The anterior temporal activation converges with the results of neuropsychological studies showing permanent retrograde amnesia following anterior temporal cortical damage and with the results of neuroimaging studies on semantic knowledge (Kapur et al, 1992;Damasio et al, 1996;Gorno-Tempini et al, 1998;Cabeza and Nyberg, 2000;Bar et al, 2001;Martin and Chao, 2001;Tsukiura et al, 2002;Thaiss and Petrides, 2003;Ploran et al, 2007). Although the right hippocampal activation during retrieval of newly learned figures followed the rule of the right hemisphere dominance in nonverbal processing (Milner, 1971;Kelley et al, 1998;Wagner et al, 1998b;Gazzaniga, 2005), the anterior temporal region did not.…”
Section: Discussionsupporting
confidence: 83%
“…The anterior temporal activation converges with the results of neuropsychological studies showing permanent retrograde amnesia following anterior temporal cortical damage and with the results of neuroimaging studies on semantic knowledge (Kapur et al, 1992;Damasio et al, 1996;Gorno-Tempini et al, 1998;Cabeza and Nyberg, 2000;Bar et al, 2001;Martin and Chao, 2001;Tsukiura et al, 2002;Thaiss and Petrides, 2003;Ploran et al, 2007). Although the right hippocampal activation during retrieval of newly learned figures followed the rule of the right hemisphere dominance in nonverbal processing (Milner, 1971;Kelley et al, 1998;Wagner et al, 1998b;Gazzaniga, 2005), the anterior temporal region did not.…”
Section: Discussionsupporting
confidence: 83%
“…Although we cannot determine from our current experimental design, prior studies of the specific cognitive processes mediated by distinct nodes of activity, such as left DLPFC, have emphasized the role of left DLPFC during successful context retrieval (Thaiss and Petrides, 2003;Dobbins et al, 2004;Mitchell et al, 2004Mitchell et al, , 2006, and have suggested that this region is involved in mediating cognitive control processes during memory retrieval, such as retrieval search, response selection, and/or postretrieval monitoring (Rajah et al, 2008). Similarly, several studies have reported greater inferior parietal cortex activity during retrieval success (Wagner et al, 2005).…”
Section: Age-related Changes In Right More Than Left Mfg Volumementioning
confidence: 93%
“…The impact of encoding task and instruction observed here is consistent with two recent behavioral studies. Thaiss and Petrides (2003), after observing an exception to the typical finding that patients with prefrontal damage perform poorly in source memory tests, argued that the high accuracy of their patients was due to explicit instruction during the encoding phase to try to learn relationships. Glisky, Polster, and Routhieaux (1995) have consistently reported that healthy older adults who perform poorly in neuropsychological tests traditionally thought to tap prefrontal function also have special difficulty with source memory tests.…”
Section: Influence Of Encoding Task During Source Memory Retrievalmentioning
confidence: 94%